The Effect of Brand Image on PT Shaza Food Product Purchase Decision (Case Study in South Tangerang Area) - Putri Nilam Kencana; Nurwita (Kusuma Negara Business School, 2020)
The purpose of this study was to determine the effect of brand image on product purchasing decisions at PT Shaza Food, a case study in the South Tangerang area and to determine whether or not the influence of Brand Image on Purchasing Decisions. This research method is a descriptive quantitative form with survey techniques. The sampling technique used random sampling technique with a total sample of 109 respondents. Data analysis used statistical tools with SPSS version 22 for windows with the analysis method of validity, reliability, normality, coefficient of determination, simple linear regression equations, and hypothesis testing. The result of hypothesis testing shows that the value of T_ (count)> T table (13.060> 1.982) so that Ho is rejected and Ha is accepted is the Brand Image (x) affects the purchase decision (y). The results of the coefficient of determination obtained R Square value of 0.614 or 61.4%, this shows that the Brand Image variable (x) has an effect on purchasing decisions (y) by 61.4%, and 38.6% is influenced by other variables outside of this research